Three new species of Neotropical Ceraleurodicus Hempel (Hemiptera: Aleyrodidae) found in the Natural History Museum (London) collection, with notes and a puparial key to species - Canty, Roy J.; Martini, Biancamaria; Wanke, Dominic (Zootaxa, 2023)
In this study, three new species of whitefly in the neotropical genus Ceraleurodicus Hempel are described and illustrated based on specimens discovered in the aleyrodid collection of the Natural History Museum, London (NHMUK): Ceraleurodicus boteh Canty sp. nov., Ceraleurodicus brianeno Canty sp. nov., and Ceraleurodicus wire Canty sp. nov. Also included is a key to puparia of the ten known species in the genus, and brief descriptions and illustrations of the known puparia and adults within the genus.